2020
DOI: 10.1096/fj.202000629r
|View full text |Cite
|
Sign up to set email alerts
|

Resident mesenchymal vascular progenitors modulate adaptive angiogenesis and pulmonary remodeling via regulation of canonical Wnt signaling

Abstract: This is an open access article under the terms of the Creative Commons Attribution-NonCommercial-NoDerivs License, which permits use and distribution in any medium, provided the original work is properly cited, the use is non-commercial and no modifications or adaptations are made.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 111 publications
(260 reference statements)
1
19
0
Order By: Relevance
“…In addition, Dkk3 is able to signal by binding the CXCR7 receptor to stimulate these Sca-1 + progenitor cells' migration [118]. Recent results on ABCG2 + mesenchymal cells suggest that Wnt activation prevents differentiation of these progenitor cells towards EC through β-catenin activation [119]. This is in line with other studies in which inhibition of Wnt signaling enhanced the angiogenic properties of endothelial-colony-forming cells [120] and stimulated the release of vasculogenic progenitor cells from bone marrow.…”
Section: Wntsupporting
confidence: 72%
“…In addition, Dkk3 is able to signal by binding the CXCR7 receptor to stimulate these Sca-1 + progenitor cells' migration [118]. Recent results on ABCG2 + mesenchymal cells suggest that Wnt activation prevents differentiation of these progenitor cells towards EC through β-catenin activation [119]. This is in line with other studies in which inhibition of Wnt signaling enhanced the angiogenic properties of endothelial-colony-forming cells [120] and stimulated the release of vasculogenic progenitor cells from bone marrow.…”
Section: Wntsupporting
confidence: 72%
“…The side population is characterized by their ability to efflux fluorescent dyes via ATP‐binding transporters such as ABCG2; and a recent study on lung resident ABCG2 + cells has identified them as mesenchymal vascular progenitors with capacity to modulate adaptive repair angiogenesis in the lung. 63 …”
Section: Markers For Endothelial Progenitorsmentioning
confidence: 99%
“…Apart from vascular remodelling via endothelial cells and smooth muscle cells, activation of WNT/β-catenin signalling has been implicated in the suppression of mesenchymal progenitor cells (MPC) differentiation into functional pericytes, thereby driving a phenotype of persistent microvascular dysfunction and abnormal angiogenesis (Gaskill et al 2017). Similarly, Summers et al suggested activation of WNT/β-catenin signalling in MPC induced emphysema-like distal lung remodelling and exacerbated vascular injury (Summers et al 2020).…”
Section: Pulmonary Vascular Diseasesmentioning
confidence: 99%